Liquid-vapor equilibrium for the Water-Acetone-Butanol-Ethanol quaternary system at Low Pressures - Moreno Cascante, Jorge Arturo; Cubillos Lobo, Jairo Antonio (Universidad Pedagógica y Tecnológica de Colombia, 2018)
Due to the ocurrence of a non ideal behavior of ethanol, butanol and acetone in aqueous solutions, a method to predict those properties in mixture that depend on the composition, temperature and pressure, especially the activity and the fugacity, is outlined in this work. These properties are very important for estimating equilibrium constants, constants of transfer speed and chemical reaction, sizing and design of process equipment. Currently, biobutanol is considered a substitute for bioethanol as a biofuel, presenting advantages, such as: higher heat capacity and lower vapor pressure. It is obtained from the fermentation of Acetone-Butanol-Ethanol (ABE), where its major products are acetone, butanol and ethanol in a molar ratio of 3: 6: 1, respectively. Therefore, the liquid-vapor equilibrium for the quaternary system water-acetone- butanol-ethanol was calculated at reduced pressures of 0.1, 0.5 and 1 kPa, with the purpose of evaluating the behavior of the azeotropes (water-butanol and water-ethanol), which is a key issue in the application of a separation process. The Non Random Two Liquid model (NRTL) was used to calculate the activity coefficient of the components in the liquid phase, the virial equations to calculate the fugacity coefficient of the components in the vapor phase and the Rachford and Rice algorithm for the dew temperature. In this way, it could be demonstrated that at low pressures the azeotrope formed between water and butanol slighly disappears while the pressure is going down. Therfore, it is recommended by using a pressure of 0.1 kPa for vacuum distillation, while 0.5 kPa for pervaportation. These values depend on the separation system stability (membranes in case of pervaporation) and the process economical balance.